The National Care Standards: hearing the voices of young people in residential care - Irene Stevens; Pauline Boyce (Scottish Journal of Residential Child Care)
The National Care Standards describe what each child or young person can expect from their residential care home in Scotland. The Scottish Commission for the Regulation of Care (SCRC) invited the Scottish Institute of Residential Child Care to carry out a study eliciting the views of young people. This article presents a selection of the findings where young people give their views about the Standards. Twenty-four young people between 15 and 19 years took part in the study, with each of the young people taking part in focus groups.